In vitro evaluation of biocontrol agents and fungicides on wood decay fungiganoderma associated with mortality of tree legumes (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment was conducted to isolate a number of biocontrol agent- Trichoderma spp. from infected spawn packets of oyster mushroom at National Mushroom Development and Extension Centre, Savar, Dhaka, Bangladesh. These bio-control agents were used as antagonist against four wild wood decay fungi of Ganoderma, viz., G. lucidum-1, G. lucidum-2, G. lucidum-3, G. applanatum and two cultivated G. lucidum-4, G.lucidum-6 under in vitro condition. An in vitro trial of Trichoderma spp. against Ganoderma were performed by dual culture, by treating with volatile, non-volatile and naturally untreated metabolites of bio-control agents. In dual culture, all the Trichoderma species showed 70- 100% mycelia inhibition of G. lucidum-1 and G. lucidum-2, 55.6-100% inhibition of G. lucidum-3, 20-66.7% of G. applanatum, 100% of G. lucidum-5, 75-100% of G. lucidum-6. Effects of heat killed extracts of Trichoderma spp. on growth of G. lucidum-2 (wild) and G. lucidum-6 (cultivated) were also evaluated. Fungicides Bavistin and Dithane M-45 were also used to investigate the mycelial growth inhibition of Ganoderma spp.Int. J. Agril. Res. Innov. & Tech. 6 (2): 31-35, December, 2016